Application of Ultrasonic Chain Pin Sensor for Soil Wind Erosion Monitoring - Zheng Shuhai; Lei Lei; Tian Kanliang; Ma Beiqing (Shuitu baochi tongbao)
[Objective] The application of ultrasonic chain pin sensor in soil wind erosion was studied by experiment to verify the monitoring accuracy and reliability of the equipment for wind erosion in order to provides a theoretical basis for the improvement and popularization of the equipment. [Methods] A wind erosion test using the ultrasonic chain pin sensor was conducted in a wind tunnel. [Results] The measurement error of the ultrasonic chain pin sensor in the wind tunnel erosion test was ±1 mm, and the measurement accuracy was very high. Measurement error changed little as wind erosion thickness increased, and the variance was only 0.04 and exhibited high stability. [Conclusion] The ultrasonic chain pin sensor had good accuracy, stability, and reliability in wind erosion monitoring, and can be used for automatic monitoring of wind erosion.